PROFIL PENGOBAT TRADISIONAL RAMUAN DAN RAMUAN OBAT HERBAL YANG DIGUNAKAN DI PROPINSI SULAWESI TENGGARA, KALIMANTAN SELATAN DAN LAMPUNG - -, Sa'roni; Winarno, Wien; -, Adjirni; -, Pudjiastuti (Badan Penelitian dan Pengembangan Kesehatan, 2011)
Traditional healers ingredients to take part in increased of public health. Therefore to find traditional healers ingredients base data to used for to treat, carry out cross-sectional design survey at three provinces those Southeast Sulawesi, South Kalimantan and Lampung with totally sample 48 every province. The results survey of traditional healers profile showed capacity sources of man in Southeast Sulawesi, South Kalimantan and Lampung yet low an education level and much traditional helers no practice yet. Showed ingredients to used for to treat public disorders there are ingredient?s to treat for cancer, diabetes mellitus, haemoroid, rheumatic, tuberculosis, stone blader, hight blood pressure, malaria and cough. Many plants for ingredients there are Curcuma xanthorrhiza Roxb, Andrographis paniculata Ness, Orthosiphon grandiflora Bold, Curcuma domestica Val, Zingiber officinale Roxb, Phaleria macrocarpa Boerl, Carica papaya L and Loranthus sp.